2013
DOI: 10.1111/hepr.12225
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter arterial chemoembolization for hepatocellular carcinoma: Comparison of the therapeutic efficacies between miriplatin and epirubicin

Abstract: For HCC patients, although miriplatin-TACE was superior to epirubicin-TACE in the short term, it proved inferior to the latter in the long term. The merits of TACE using miriplatin should be further investigated, because adverse effects appear to be minimal after miriplatin administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The prospective study design and rigid evaluation are strengths in the present study. Prior to this study, there were three retrospective studies that compared the local control efficacy of TACE for HCC with miriplatin or epirubicin . In those studies, one study showed that the local control effects of TACE for HCC using miriplatin was significantly less than those using epirubicin .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prospective study design and rigid evaluation are strengths in the present study. Prior to this study, there were three retrospective studies that compared the local control efficacy of TACE for HCC with miriplatin or epirubicin . In those studies, one study showed that the local control effects of TACE for HCC using miriplatin was significantly less than those using epirubicin .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it cannot sufficiently flow into small feeding arteries of the tumor because of that high viscosity of the miriplatin–iodized oil suspension . In the previous controlled studies, a warmed miriplatin–iodized oil suspension was not administered . Seko et al reported the efficacy of TACE using miriplatin according to temperature conditions, for example, 44.3% of the patients treated with room temperature miriplatin, and 71.1% of the patients who received warmed miriplatin experienced CR or PR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that the local control rate is higher with epirubicin compared with miriplatin (22). However, the short-term effects of miriplatin and epirubicin are reported to be comparable (23). In the present study of BCLC-B HCC, in terms of tumor factors, it was clear that up-to-seven criteria and hepatic reserve play a role in survival; in terms of tumor treatment factors, the combined use of DDP-H and miriplatin contributed to improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…Miriplatin ([SP‐4‐2]‐[(1R, 2R)‐Cyclohexane‐1,2‐diamine‐N,N′]‐bis (tetradecanoato‐O) platinum monohydrate (Dainippon Sumitomo Pharmaceutical Co. Ltd., Osaka, Japan) is a novel lipophilic cisplatin derivative that can be suspended in lipiodol, an oily lymphographic agent . Several studies have reported the usefulness of miriplatin at the time of TACE therapy for HCC . Although miriplatin seemed to have an ideal chemical and pharmacological structure in the treatment of HCC with lipiodol‐using TACE, Miyayama et al .…”
Section: Introductionmentioning
confidence: 99%